Optimal sunscreen use allows vitamin D synthesis. (1st November 2019) - Young, A.R.; Narbutt, J.; Harrison, G.I.; Lawrence, K.P.; Bell, M.; O'Connor, C.; Olson, P.; Grys, K.; Baczynska, K.A.; Rogowski‐Tylman, M.; Wulf, H.C.; Lesiak, A.; et al.
Summary: Vitamin D, vital for bone health, is produced by the skin in response to ultraviolet radiation (UVR) from sunlight. However, as well as being the main source of vitamin D, UVR is a major cause of skin cancer. This has led to questions about how to prevent low levels of vitamin D whilst limiting the risk of skin cancer. This study, led by researchers from King's College London, found that use of sunscreen did not prevent most people from getting enough vitamin D whilst on a week‐long holiday to an area with a very high UV index. Whilst on holiday, 20 people received a broad‐spectrum sunscreen with a Sun Protection Factor (SPF) of 15, offering UVB protection and high UVA protection. Another 20 received a non‐broad‐spectrum sunscreen, also SPF 15 but with low UVA protection. These two groups were told how to use their sunscreens correctly to achieve the labelled SPF. In contrast, 22 people used their own sunscreen with no instructions on application, and 17 people formed a control group who remained in Poland. Blood samples were taken from participants 24 hours before and 24 to 48 hours after the holiday to check vitamin D levels. The first two groups saw a highly significant improvement in vitamin D levels. The group that used their own sunscreens also had significant vitamin D synthesis, but all had sunburn. During the same period, the control group had a slight decline in vitamin D. Abstract : Linked Article:  Young et al. Br J Dermatol 2019; 181 :1052–1062